Um estudo sobre a ouvidoria da Universidade Federal do Pará: contribuições e desafios - ROCHA, Iraneide Evangelista (Universidade Federal do Pará, 2014)
The following text presents a research carried on the Ombudsman Office of the Federal University of Pará, in the period 2006-2012, aiming to investigate the way that that office has been performing its duties and responsibilities, in the relationships amongst the university community. In order to achieve these goals, it has been determined the exploratory descriptive research as the methodological procedure, as well as the bibliographical and documentary modalities. Authors such as Rousseau, Schumpeter, Lyra, Vilanova and others, were used to define concepts of analysis, such as: state, democracy, public ombudsman. As a result of that research, it has been exposed some initial considerations that express the importance of the Ombudsman Office of UFPA for the university community, perceived as an instrument of mediation and democratization of access, in the search of the efficiency of the services offered by the institution.